Futsal Shooting Skill Level and Dominant Physical Condition in Extracurricular Activities of State Middle School 1 Batu Sopang, Paser Regency, East Kalimantan - Ahmad Hidayat; Ramadhan Arifin; Mita Erliana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the level of futsal shooting skills and dominant physical conditions of extracurricular participants at State Middle School 1 Batu Sopang, Paser Regency, East Kalimantan. The method used is descriptive quantitative with a futsal shooting skills measurement test and a dominant physical condition test of futsal extracurricular participants at State Middle School 1 Batu Sopang, Paser Regency, East Kalimantan. The results of the study showed that most participants had a shooting skill level in the enough category, which was 10 people (80%), and a good category of 2 people (20%). The results of the overall physical condition test were in the enough category (with a conversion value of 6). The conclusion of the results of the study of the level of futsal shooting skills and dominant physical conditions of extracurricular participants at Middle School Negeri 1 Batu Sopang, Paser Regency, East Kalimantan, the average shooting skill level was enough and the results of the physical condition test were in the enough category.